DIPLOMASI DAN JAKARTA-JAPAN MATSURI - Cahyani, Ragilya; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The long-standing relationship between Indonesia and Japan has prompted Japan to maintain its diplomacy with Indonesia comprehensively. Japan recognizes that its public diplomacy in Indonesia is not yet optimal. Therefore, Japan needs to enhance its diplomacy through culture. While Japanese culture is already widely known among the Indonesian population, there are still many Indonesians who are not entirely familiar with it. This research aims to examine the role of Jakarta-Japan Matsuri in Japanese public diplomacy in Indonesia. The research is written using Edmund Gullion's theory of public diplomacy, which asserts that public diplomacy is a nation's effort to advance its national interests by fostering an understanding of the attitudes, culture, and policies of other countries with the goal of ensuring that the public holds a favorable view of a nation, providing a social foundation for building relationships and expanding national interests. From the results of this research, it can be concluded that through Jakarta-Japan Matsuri, Japan can boost its public diplomacy by providing an authentic Japanese festival experience, engaging in cultural exchanges, and strengthening its friendship with Indonesia. Keywords: culture, diplomacy, public, team work